Hepatic resection versus transarterial chemoembolization in infiltrative hepatocellular carcinoma: A multicenter study. Issue 12 (14th May 2020) - Wang, Yuanqi; Shen, Jingxian; Feng, Shiting; Liang, Ruiming; Lai, Jiaming; Li, Dongming; Peng, Baogang; Wang, Zaiguo; Huang, Cheng; Kuang, Ming
Abstract: Background and Aim: Prognosis of infiltrative hepatocellular carcinoma (iHCC) is poor, and the treatments selection based on efficacy is unclear. We performed this multicenter study to compare the efficacy of hepatic resection and transarterial chemoembolization (TACE) in treating patients with iHCC. Methods: We retrospectively analyzed the overall survivals (OS) in 319 patients with iHCC who were initially treated by hepatic resection ( n  = 133) or TACE ( n  = 186) at four tertiary centers. Fifty‐eight patients in the TACE group were assessed as resectable and compared with the hepatic resection group in subgroup analysis. A propensity score matched (PSM) analysis was performed to reduce selection bias. Cox regression was performed to identify significant factors associated with OS. Results: The median OS time was significantly longer in the hepatic resection group than that in the TACE group, before and after PSM (before PSM, 17.5 vs 7.3 months, P  < 0.0001; after PSM, 14.0 vs 7.3 months, P  < 0.0001). The multivariable analysis indicated TACE as a risk factor of OS (hazard ratio = 2.233, 95% confidence interval = 1.492 to 3.341, P  < 0.0001), as well as portal venous tumor thrombosis grades 3–4 and alpha fetal protein (AFP) > 400 ng/mL. In the subgroup analysis, the better efficacy of hepatic resection over TACE persisted regardless of the grade of portal venous tumor thrombosis and the level of AFP. As for resectable patients, hepatic resection still showed significant survival benefit (before PSM, 17.5 vs 11.2 months, P =  0.0013; after PSM, 14.0 vs 10.9 months, P =  0.0304). Conclusion: Hepatic resection might be the better choice for patients with iHCC due to its better survival benefit than TACE.